Tea Tree Oil: Properties and the Therapeutic Approach to Acne-A Review - Tânia Nascimento; Diana Gomes; Ricardo Simões; Maria da Graça Miguel (MDPI AG, 2023)
Acne vulgaris is an inflammatory dermatological pathology that affects mostly young people. However, it can also appear in adulthood, mainly in women. It has a high psychosocial impact, not only at the time of active lesions but also due to the consequences of lesions such as scarring and hyperpigmentation. Several factors are involved in the physiopathology of acne and the constant search for active ingredients is a reality, namely phytotherapeutic ingredients. Tea tree oil is an essential oil extracted from Melaleuca alternifolia (Maiden & Betch) Cheel with known antibacterial, anti-inflammatory, and antioxidant properties, making it a candidate for the treatment of acne. This review aims to describe the various properties of tea tree oil that make it a possible ingredient to use in the treatment of acne and to present several human studies that have evaluated the efficacy and safety of using tea tree oil in the treatment of acne. It can be concluded that tea tree oil has good antibacterial, anti-inflammatory, and antioxidant properties that result in a decrease in the number of inflammatory lesions, mainly papules, and pustules. However, given the diversity of study designs, it is not possible to draw concrete conclusions on the efficacy and safety of this oil in the treatment of acne.